Спосіб підвищення післяремонтної довговічності шестеренних насосів - Дідур, В. В.; Паніна, Валерія Валеріївна; Панина, Валерия Валерьевна; Panina, Valeriia; В'юник, Ольга Володимирівна; Вьюник, Ольга Владимировна; Viunyk, Olha (ТДАТУ, 2019)
UK: Працездатність і ресурс сільськогосподарських машин в значній мірі визначаються інтенсивністю зношування деталей тертя. Досвід експлуатації свідчить, що 80-90% деталей машин виходять з ладу через знос. Відомо, що правильно вибравши матеріал і покриття трібоспряжень, можна значно підвищити зносостійкість і довговічність вузлів тертя при експлуатації. Оптимізація вибору покриттів вузлів тертя мобільних сільськогосподарських машин є найбільш перспективним і економічним шляхом підвищення їх працездатності і ресурсу. Пропонується підвищення довговічності шестеренних насосів гідравлічних систем мобільних сільськогосподарських машин та забезпечення працездатності пар тертя, за рахунок металоплакируючих нанодисперсних присадок, в результаті яких збільшується ресурс та ефективність використання шестеренчастих насосів. RU: Работоспособность и ресурс сельскохозяйственных машин в значительной степени определяются интенсивностью износа деталей трения. Опыт эксплуатации показывает, что 80-90% деталей машин выходят из строя из-за износа. Известно, что правильно выбрав материал и покрытие трибосоединений, можно значительно повысить износостойкость и долговечность узлов трения при эксплуатации. Оптимизация выбора покрытий узлов трения мобильных сельскохозяйственных машин является наиболее перспективным и экономичным путем повышения их работоспособности и ресурса. Предлагается повышение долговечности шестеренных насосов гидравлических систем мобильных сельскохозяйственных машин и обеспечения работоспособности пар трения, за счет металоплакируючих нанодисперсных присадок, в результате которых увеличивается ресурс и эффективность использования шестеренчатых насосов. EN: Тhe efficiency and resource of agricultural machines is largely determined by the intensity of wear of the friction parts. Operating experience shows that 80-90% of machine parts fail due to wear and tear. It is known that by properly selecting the material and the coating of the tribes, it is possible to significantly increase the wear resistance and durability of the friction units during operation. Optimizing the choice of friction units for mobile agricultural machines is the most promising and economical way to increase their efficiency and resource. In the period of bench rolling it is necessary to reduce wear during the working-in period. This can be done by properly selecting the rolling modes of hydraulic transmissions of mobile machines, using new technologies that involve the use of surfactants for working out. It is proposed to increase the longevity of gear pumps of hydraulic systems of mobile agricultural machines and to ensure the efficiency of friction pairs, due to metal-clad nanodispersed additives, which increases the resource and efficiency of the use of gear pumps. The service life of gear pumps of hydraulic systems and their overhaul life depends on the quality of working of their parts in the period of after-repair run-in. The acceleration of the workpiece can be done by properly selecting the modes of rolling-in of hydraulic units, the use of new technologies, the use of working additives. The analysis of used additives for working out hydraulic parts after repair has revealed the most promising use of complex additives containing surfactants and reactive substances.
Способ повышения послеремонтной долговечности шестеренных насосов
Method of improvement of post-repair durability of gear pumps
Keywords: шестеренні насоси; припрацювання; ФАБО; поверхнево-активні речовини; присадка; експертна оцінка; шорсткість; фактори; шестеренные насосы; приработка; поверхностно-активные вещества; экспертная оценка; шероховатость; факторы; gear pumps; working out; FABO; surfactants; additive; expert judgment; roughness; factors